2016
DOI: 10.1371/journal.pone.0154372
|View full text |Cite
|
Sign up to set email alerts
|

Medical Team Evaluation: Effect on Emergency Department Waiting Time and Length of Stay

Abstract: Emergency Departments (ED) are trying to alleviate crowding using various interventions. We assessed the effect of an alternative model of care, the Medical Team Evaluation (MTE) concept, encompassing team triage, quick registration, redesign of triage rooms and electronic medical records (EMR) on door-to-doctor (waiting) time and ED length of stay (LOS). We conducted an observational, before-and-after study at an urban academic tertiary care centre. On July 17th 2014, MTE was initiated from 9:00 a.m. to 10 p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 53 publications
2
46
1
2
Order By: Relevance
“…A number of studies show increased efficiency with changes in front‐end operations, mostly focusing on rapid triage and physician/provider in triage . At the same time, a systematic review showed no statistically significant decrease in LOS with team triage, and other studies show improvements only with certain patient acuity levels . Although this study on swarming was not designed to quantify an improvement in efficiency metrics, our findings showed an average time commitment of approximately 10 minutes for the physicians, suggesting that a substantial amount can be accomplished in regard to patient care, communication, and education in a relatively short time frame.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…A number of studies show increased efficiency with changes in front‐end operations, mostly focusing on rapid triage and physician/provider in triage . At the same time, a systematic review showed no statistically significant decrease in LOS with team triage, and other studies show improvements only with certain patient acuity levels . Although this study on swarming was not designed to quantify an improvement in efficiency metrics, our findings showed an average time commitment of approximately 10 minutes for the physicians, suggesting that a substantial amount can be accomplished in regard to patient care, communication, and education in a relatively short time frame.…”
Section: Discussionmentioning
confidence: 62%
“…In many of the physician‐in‐triage or team triage models, the team that performs the initial assessment is typically not the definitive treatment team . When one provider sees a patient in triage, with a different provider for the remainder of the ED stay, this increases hand‐offs and may also increase the diagnostic studies ordered by the initial triage provider . In the swarming model, the team responsible for the initial assessment is the primary care team for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Waiting time represents the services that an ED can provide, and is one of the measurable key performance indicators in hospitals. 28 However, research on emergency waiting time in China is scarce. Comparing absolute waiting time between patients is difficult to interpret because of the difference in severity.…”
Section: Discussionmentioning
confidence: 99%
“…La medición horaria de Crowding a través de la escala de NEDOCS aporta información irremplazable para la toma de decisiones. Las centrales de emergencias están tratando de aliviar el Crowding mediante diversas intervenciones 14,15 . En un futuro, la potencial generación de un sistema que permitiera la medición en tiempo real del grado de Crowding en la CE, podría brinda una herramienta irremplazable para la gestión y por ende, para la seguridad de los pacientes 16 .…”
Section: Discussionunclassified